D3O-based protective layer structure and preparation method thereof

By using D3O materials and a variety of other materials in the protective layer structure, a multifunctional protective layer is formed, which solves the problem that traditional protective layer cannot provide comprehensive protection when collisions between special-shaped objects and sharp objects, and achieves a comprehensive effect of energy absorption, protection and wear resistance.

CN119682336APending Publication Date: 2025-03-25CHINA RAILWAY SIGNAL & COMM SHANGHAI ENG BUREAU GRP

Patent Information

Application Number
CN202411914042.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The traditional protective layer structure cannot provide comprehensive protection when facing collisions between special-shaped objects and sharp objects, and its protection is relatively single, which cannot meet the needs of multifunctions.

Method used

A protective layer structure based on D3O is adopted, and a protective layer with various functions such as energy absorption, protection, wear resistance, etc. is formed by using a variety of materials in the inner layer, outer layer and inner honeycomb tube bundle layer.

Benefits of technology

It realizes the performance of dispersing impact force, absorbing and buffering impact kinetic energy and anti-friction. It is suitable for protective facilities or armor directly facing the human body, improving the protective effect and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119682336A_ABST
    Figure CN119682336A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of protection. The invention provides a D3O-based protective layer structure and a preparation method thereof. The D3O-based protective layer structure comprises an inner layer, an inner tube bundle layer and an outer layer which are sequentially arranged in parallel from bottom to top, the inner layer comprises a polyester fabric and an organic silicon resin based nano titanium boride and titanium carbide composite coating coated on the polyester fabric; the internal honeycomb-shaped tube bundle layer comprises a honeycomb-shaped frame body formed by a thermoplastic elastomer and a filler filled in the frame body, and the filler is a D30 material; and the outer layer is a butyl rubber layer. The single protective property of a traditional protective layer is changed, the performance of multiple composite materials is combined, the protective layer with multiple functions of wear resistance, softness, hardness, elasticity and the like is formed, and the protective layer has the performance of dispersing impact force, absorbing and buffering impact kinetic energy and preventing friction and can be applied to preparation of facilities or protective tools directly facing human body protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of protection technology, and in particular relates to a D3O-based protection layer structure and a preparation method thereof. Background Art

[0002] With the progress and development of society, more and more industrial equipment and personnel are inevitably subject to collisions while in motion, and a protective layer is needed to ensure the safety of personnel or equipment. Safety plays a vital role in all industries, so the various technologies used in safety protection also need special attention.

[0003] Traditional protective layer structures are mostly of two types, soft and hard. These two types of protection are not suitable for all scenarios. When the protected object is irregular and is hit by a sharp object, the hard protective layer cannot provide comprehensive protection, and the soft protective layer cannot block the collision of sharp objects.

[0004] The non-Newtonian fluid expansion foam D30 material is an impact-resistant material made of viscose liquid and a polymer. It has two states, hard and soft, under different impacts. It remains relaxed, soft and elastic under normal conditions. Once it is violently impacted or squeezed, the molecules immediately lock with each other, quickly tighten and harden to absorb the external force, forming a protective layer. When the external force disappears, the material will return to its original relaxed soft elastic state. It can respond differently to different impact situations within nanoseconds.

[0005] The traditional protective layer structure has a relatively simple protective property. The present invention proposes a protective layer structure based on D3O, which not only has the function of energy absorption, but also can meet the requirements of protection and wear resistance. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a D3O-based protective layer structure and a preparation method thereof. The present invention changes the single protective property of the traditional protective layer and utilizes a variety of materials to form a protective layer with multiple functions such as wear resistance, softness, hardness, and elasticity. The protective layer has the properties of dispersing impact force, absorbing and buffering impact kinetic energy, and preventing friction, and can be used in the preparation of facilities or protective gear directly facing human body protection.

[0007] The object of the present invention is to provide a D3O-based protective layer structure, comprising an inner layer, an internal tube bundle layer, and an outer layer arranged in parallel from bottom to top, the inner layer comprising polyester fabric and a silicone resin-based nano-titanium boride and titanium carbide composite coating coated on the polyester fabric, the internal honeycomb tube bundle layer comprising a honeycomb frame formed of a thermoplastic elastomer and a filler filled in the frame, the filler being a D30 material, and the outer layer being a butyl rubber layer.

[0008] The D3O-based protective layer structure of the present invention has the performance of protection, energy absorption and wear resistance, and its inner layer has excellent wear resistance and tensile strength while being in contact with the protected object.

[0009] In the present invention, the coating used for the inner layer of the organic silicon resin-based nano-titanium boride and titanium carbide composite coating comprises the following components in percentage by mass:

[0010] Silicone resin 65-75%

[0011] Anhydrous ethanol 15-25%

[0012] Hyperdispersant 0.5-5%

[0013] Ethanol thickener 0.5-5%

[0014] Nano titanium boride 0.5-5%

[0015] Nano titanium carbide 0.5-3%

[0016] The sum of the mass percentages of the above components is one hundred percent.

[0017] The coating amount of the organic silicon resin-based nano-titanium boride and titanium carbide composite coating applied on one side of the polyester fabric is 10-25g / m 2 .

[0018] When applied to polyester fabric, the coating forms a coating that significantly improves wear resistance and tensile strength.

[0019] The coating used for the organic silicon resin-based nano-titanium boride and titanium carbide composite coating can be applied to one or both sides of the polyester fabric. The polyester fabric can be covered with the organic silicon resin-based nano-titanium boride and titanium carbide composite coating on both sides. When the protected object is skin tissue such as human body, the only contact protected object is the polyester fabric.

[0020] Preferably, the coating used for the inner layer of the organic silicon resin-based nano-titanium boride and titanium carbide composite coating comprises the following components in percentage by mass:

[0021] Silicone resin 69.75%

[0022] Anhydrous ethanol 23.25%

[0023] Hyperdispersant 1.5%

[0024] Ethanol thickener 1.5%

[0025] Nano titanium boride 2.67%

[0026] Nano titanium carbide 1.33%,

[0027] The coating amount of the organic silicon resin-based nano-titanium boride and titanium carbide composite coating applied on one side of the polyester fabric is 15-16g / m 2 .

[0028] The tensile breaking strength of polyester fabric with silicone resin-based nano-titanium boride and titanium carbide composite coating is increased from 573.92N to 620.48N, and the bursting strength is increased from 652.34N to 790.07N. The hydrophobicity is greatly improved, and the contact angle can reach more than 120°.

[0029] Furthermore, the method for preparing the coating used for the above-mentioned organic silicon resin-based nano-titanium boride and titanium carbide composite coating comprises the steps of:

[0030] (1) Weigh each component according to the above ratio, and heat the silicone resin to 50-60° C. under stirring to soften it;

[0031] (2) adding silicone resin and anhydrous ethanol to a container, stirring at a speed of 300-500 r / min for 10-15 minutes, adding a hyperdispersant and an ethanol thickener, stirring for 20-30 minutes, and forming a mixed solution;

[0032] (3) Slowly adding nano titanium boride and nano titanium carbide into the above mixed solution, while increasing the stirring speed to 800-1000 r / min, and continuing stirring for 30-45 minutes to obtain a coating for an organosilicon resin-based nano titanium boride and titanium carbide composite coating.

[0033] In the present invention, the honeycomb frame is a hexagonal frame, and the height of the frame is higher than the filled material. The filling material is prevented from overflowing outside the frame, ensuring uniform coverage of the filling material, and the thermoplastic elastic plastic material also provides a certain buffer force for collision. The quadrilateral space formed between each honeycomb frame is filled with D30 material.

[0034] Furthermore, a fixed protection position is provided on the protective layer, an outer protective layer is provided at the fixed protection position, and the outer protective layer includes a high-density polyethylene plastic layer and a polyurethane coating coated on the high-density polyethylene plastic layer.

[0035] Preferably, the thickness of the inner layer is 1-2mm, wherein the thickness of the polyester fabric is 1-1.8mm, and the thickness of the organic silicon resin-based nano-titanium boride and titanium carbide composite coating is 0.05-0.35mm; the thickness of the outer layer is 2-4mm; the height of the honeycomb frame of the inner honeycomb tube bundle layer is 3.5-5mm, wherein the height of the D3O material filled inside is 2-3mm; the overall thickness of the outer protective layer is 4-5mm, wherein the thickness of the polyethylene plastic layer is 3-4mm, and the thickness of the polyurethane coating is 1-2mm. The bottom thickness of the quadrilateral space formed between the honeycomb frames is 1-2mm.

[0036] The method for preparing the D3O-based protective layer structure comprises the following steps:

[0037] (1) Preparation of the inner layer: spray the coating used for the organic silicon resin-based nano-titanium boride and titanium carbide composite coating on the polyester fabric, dry it naturally for 3-5 hours, and make the coating evenly adhere to the polyester fabric to form an organic silicon resin-based nano-titanium boride and titanium carbide composite coating; or immerse the polyester fabric in the coating, take it out after immersion for 80-110 minutes, dry it naturally for 3-5 hours, and make the coating evenly adhere to the polyester fabric to form an organic silicon resin-based nano-titanium boride and titanium carbide composite coating;

[0038] (2) Preparation of the internal honeycomb tube bundle layer: The thermoplastic elastomer TPE material is melted and injected into the honeycomb tube bundle layer mold cavity. After curing, D3O material is filled in the hexagonal frame, and the height of the D30 material is 1-2 mm lower than the hexagonal frame;

[0039] (3) Preparation of the outer protective layer: dust, oil and other impurities are removed from the surface of the polyethylene plastic, the surface is polished with coarse sandpaper, and then the surface is finely polished with fine sandpaper to clean the dust on the surface, and a polyurethane roller is applied to the surface of the polyethylene plastic, and cured by heating or ultraviolet light;

[0040] (4) The inner layer, the inner honeycomb tube bundle layer, the outer layer and the outer protective layer are stacked and arranged in sequence, and an adhesive is used to bond them at the joints. The adhesive is cured by flat plate pressing to obtain a protective layer.

[0041] Preferably, in the above step (3), the coarse sandpaper is P120 and the fine sandpaper is P400.

[0042] In the present invention, the outer layer is a butyl rubber layer IIR, which can transmit the force generated by the collision to the internal honeycomb tube bundle layer, and can also bear and buffer the force transmitted from the outer protective layer. Since the butyl rubber material has energy absorption and damping properties at high deformation speed, it can provide good buffering and transmit the remaining force to the internal honeycomb tube bundle layer. In the event of a slight collision, the D3O will not harden, thereby not affecting portability and mobility.

[0043] The outer protective layer only covers the fixed protection positions. The high-density polyethylene plastic has high hardness, rigidity and strength, and can protect important fixed positions. The polyurethane coating has the characteristics of wear resistance and corrosion resistance, which can effectively protect the polyethylene plastic from damage by environmental factors, while enhancing the hardness and durability of the polyethylene plastic.

[0044] The internal honeycomb tube bundle layer is made of thermoplastic elastomer TPE material. The hexagonal frames formed are higher than the filling material, and the filling material is divided into areas to prevent the filling material from overflowing out of the frame and ensure uniform coverage of the filling material. At the same time, the thermoplastic elastic plastic material also provides a certain buffering force for collision.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The protective layer structure based on D3O of the present invention has the functions of protection, energy absorption and wear resistance. The inner layer is more suitable for contacting the human body, and the soft rubber material of the outer layer can play a better buffering role. The outer protective layer is covered at a fixed protection position, which plays the role of normal hard protection, wear resistance, corrosion resistance, etc.;

[0047] (2) When the overall protective layer is not hit or the non-Newtonian fluid expansion foam D30 material is hit with a small impact force, the overall protective layer is soft and better wraps the protected object. When it is hit by a sharp object or other strong impact, the overall protective layer is converted into hard protection to prevent the collision object from tearing and damaging the protected object;

[0048] (3) The inner layer is polyester fabric with a silicone resin-based nano-titanium boride and titanium carbide composite coating. Compared with polyester fabric, its tensile breaking strength is increased from 573.92N to 620.48N, and its bursting strength is increased from 652.34N to 790.07N. Its wear resistance and tensile strength are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 Schematic diagram of the D3O-based protective layer structure;

[0050] Figure 2 It is a schematic diagram of the inner structure;

[0051] Figure 3 It is a schematic diagram of the structure of the outer protective layer;

[0052] Figure 4 Schematic diagram of the internal honeycomb tube bundle layer.

[0053] In the figure: 1. Inner layer; 2. Outer layer; 3. Outer protective layer; 4. Internal honeycomb tube bundle layer; 5. D3O material; 21. Polyester fabric; 22. Silicone resin-based nano-titanium boride and titanium carbide composite coating; 31. High-density polyethylene plastic; 32. Polyurethane coating. DETAILED DESCRIPTION

[0054] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Example 1

[0056] 1a. Preparation of nano-titanium boride and titanium carbide composite coating based on silicone resin

[0057] Weigh the following components in mass percentage: the sum of the mass percentage of silicone resin and anhydrous ethanol is 93%, and the mass ratio of silicone resin to anhydrous ethanol is 75:25; the mass percentage of super dispersant is 1.5%; the mass percentage of ethanol thickener is 1.5%; the mass percentage of nano-titanium boride and titanium carbide is 4%, and the usage ratio of nano-titanium boride and titanium carbide is 2:1.

[0058] Ensure that all raw materials are of analytical grade and dry them before use to remove any moisture. Heat the silicone resin to 50-60°C under stirring to soften it fully for subsequent mixing operations. Add 69.75% silicone resin and 23.25% anhydrous ethanol in proportion to the container, start the agitator, and stir at 300-500r / min for 10-15 minutes to mix the two thoroughly. Then add 1.5% hyperdispersant and 1.5% ethanol thickener, and continue stirring for 20-30 minutes until a uniform and stable mixed solution is formed. Slowly add 2.67% nano-titanium boride and 1.33% nano-titanium carbide to the above solution, while increasing the stirring speed to 800-1000r / min and stirring for 30-45 minutes. This step needs to be careful to avoid agglomeration of nanoparticles. Hyperdispersants help to evenly disperse nanoparticles in the solution. Choose a suitable coating method according to the shape and size of the substrate material.

[0059] 1b. Preparation of the inner layer

[0060] The organic silicon resin-based nano-titanium boride and titanium carbide composite coating prepared above is sprayed on the polyester fabric, and then waited for 4 hours for natural drying to make the coating evenly adhere to the polyester fabric to form an organic silicon resin-based nano-titanium boride and titanium carbide composite coating.

[0061] Or the polyester fabric is immersed in the silicone resin-based nano-titanium boride and titanium carbide composite coating, and is taken out after being immersed for about 100 minutes, and is allowed to dry naturally for 4 hours, so that the coating is evenly attached to the polyester fabric to form the silicone resin-based nano-titanium boride and titanium carbide composite coating.

[0062] Through one of the above two methods, the coating amount of the organic silicon resin-based nano boride titanium carbide composite coating attached to the surface of one side of the polyester fabric is 16g / m 2 .

[0063] 2. Preparation of outer protective layer

[0064] First, dust, oil and other impurities are removed from the surface of the polyethylene plastic. P120 coarse sandpaper is used to evenly grind the surface of the polyethylene plastic to remove surface unevenness and burrs. P400 fine sandpaper is used to finely grind the surface of the polyethylene plastic to increase surface roughness. Compressed air is used to clean the dust on the surface of the polyethylene plastic. A polyurethane coating material formed by a mixture of polyols, isocyanates, catalysts, silicone modifiers and other materials is roller-coated on the surface of the polyethylene plastic. The polyurethane coating material applied to the surface of the polyethylene plastic is cured by heating or ultraviolet light.

[0065] 3. Preparation of internal honeycomb tube bundle layer

[0066] The frame of the internal honeycomb tube bundle layer is a thermoplastic elastic plastic TPE. The TPE material is melted and in a fluid state and then injected into the mold cavity of the honeycomb tube bundle layer. When the injection temperature is 30°C, it can be solidified after cooling for 2 minutes. After the internal honeycomb tube bundle layer is solidified, D3O material is filled in the hexagonal frame respectively. The D30 material is filled to 1 mm below the hexagonal frame, and the quadrilateral space formed between each honeycomb frame is filled with D30 material.

[0067] 4. Preparation method of D3O-based protective layer

[0068] The outer layer is made of butyl rubber, and the inner layer, the internal honeycomb tube bundle layer, the outer layer and the outer protective layer are stacked and arranged in sequence, and adhesives are used to bond them at the joints, and the adhesives are cured by flat plate pressing.

[0069] The overall thickness of the inner layer of the prepared protective layer is 1-2mm, wherein the thickness of the polyester fabric is 1-1.8mm, and the thickness of the silicone resin-based nano-titanium boride and titanium carbide composite coating is about 0.2mm; the bottom thickness of the honeycomb frame of the internal honeycomb tube bundle layer is 2mm, the bottom thickness of the quadrilateral space is 2mm, the frame thickness is 2mm, the frame height is 4mm, wherein the height of the internally filled D3O material is 2-3mm; the thickness of the outer layer is 3mm; the overall thickness of the outer protective layer is 4-5mm, wherein the thickness of the polyethylene plastic layer is 3-4mm, and the thickness of the polyurethane coating is about 1-2mm.

[0070] Example 2

[0071] 1a. The preparation of the organosilicon resin-based nano-titanium boride and titanium carbide composite coating is the same as that in Example 1.

[0072] 1b. Preparation of the inner layer

[0073] Spray the organosilicon resin-based nano-titanium boride and titanium carbide composite coating on the polyester fabric, wait for 3 hours to dry naturally, so that the coating is evenly attached to the polyester fabric to form an organosilicon resin-based nano-titanium boride and titanium carbide composite coating. Or immerse the polyester fabric in the titanium boride and organosilicon resin-based nano-titanium boride and titanium carbide composite coating, immerse for about 80 minutes, then take it out, wait for 3 hours to dry naturally, so that the coating is evenly attached to the polyester fabric to form an organosilicon resin-based nano-titanium boride and titanium carbide composite coating.

[0074] Through one of the above two methods, the coating amount of the organic silicon resin-based nano boride titanium carbide composite coating attached to the surface of one side of the polyester fabric is 16g / m 2 .

[0075] 2. Preparation of outer protective layer

[0076] First, dust, oil and other impurities are removed from the surface of the polyethylene plastic. P100 coarse sandpaper is used to evenly grind the surface of the polyethylene plastic to remove surface unevenness and burrs. P320 fine sandpaper is used to finely grind the surface of the polyethylene plastic to increase surface roughness. Compressed air is used to clean the dust on the surface of the polyethylene plastic. A polyurethane coating material formed by a mixture of polyols, isocyanates, catalysts, silicone modifiers and other materials is roller-coated on the surface of the polyethylene plastic. The polyurethane coating material applied to the surface of the polyethylene plastic is cured by heating or ultraviolet light.

[0077] 3. Preparation of internal honeycomb tube bundle layer

[0078] The frame of the internal honeycomb tube bundle layer is a thermoplastic elastic plastic TPE. The TPE material is melted and in a fluid state and then injected into the honeycomb tube bundle layer mold cavity. When the injection temperature is 40°C, it can be solidified after cooling for 3 minutes. After the internal honeycomb tube bundle layer is solidified, D3O material is filled in the hexagonal frame, and the D30 material is filled to 1.5 mm below the hexagonal frame.

[0079] 4. The preparation method of the D3O-based protective layer is the same as that in Example 1.

[0080] Example 3

[0081] 1a. The preparation of the organosilicon resin-based nano-titanium boride and titanium carbide composite coating is the same as that in Example 1.

[0082] 1b. Preparation of the inner layer

[0083] Spray the organosilicon resin-based nano-titanium boride and titanium carbide composite coating on the polyester fabric, wait for 2 hours to dry naturally, so that the coating is evenly attached to the polyester fabric to form an organosilicon resin-based nano-titanium boride and titanium carbide composite coating. Or immerse the polyester fabric in the organosilicon resin-based nano-titanium boride and titanium carbide composite coating, immerse for about 60 minutes, then take it out, wait for 2 hours to dry naturally, so that the coating is evenly attached to the polyester fabric to form an organosilicon resin-based nano-titanium boride and titanium carbide composite coating.

[0084] Through one of the above two methods, the coating amount of the organic silicon resin-based nano boride titanium carbide composite coating attached to the surface of one side of the polyester fabric is 16g / m 2 .

[0085] 2. Preparation of outer protective layer

[0086] First, dust, oil and other impurities are removed from the surface of the polyethylene plastic. P80 coarse sandpaper is used to evenly grind the surface of the polyethylene plastic to remove surface unevenness and burrs. P240 fine sandpaper is used to finely grind the surface of the polyethylene plastic to increase surface roughness. Compressed air is used to clean the dust on the surface of the polyethylene plastic. A polyurethane coating material formed by a mixture of polyols, isocyanates, catalysts, silicone modifiers and other materials is roller-coated on the surface of the polyethylene plastic. The polyurethane coating material applied to the surface of the polyethylene plastic is cured by heating or ultraviolet light.

[0087] 3. Preparation of internal honeycomb tube bundle layer

[0088] The frame of the internal honeycomb tube bundle layer is a thermoplastic elastic plastic TPE. The TPE material is melted and in a fluid state and then injected into the mold cavity of the honeycomb tube bundle layer. When the injection temperature is 50°C, it can be solidified after cooling for 4 minutes. After the internal honeycomb tube bundle layer is solidified, D3O material is filled in the hexagonal frame, and the D30 material is filled to 2mm below the hexagonal frame.

[0089] 4. The preparation method of the D3O-based protective layer is the same as that in Example 1.

[0090] Protective performance test

[0091] The inner layer, outer protective layer, and internal honeycomb tube bundle layer obtained in Examples 1-3 were tested for their protective performance effects, respectively; and the protective performance of the D3O-based protective layer structure compared with existing protective materials within a temperature range of -4°C to 122°C.

[0092] 1. Comparison of physical properties of inner coating

[0093] The physical properties of the coatings obtained by spraying the coatings onto polyester fabrics are compared as shown in the following table.

[0094]

[0095] It can be seen from the test results in the table that the coating naturally dried for 4 hours in Example 1 has uniform and dense quality and excellent performance.

[0096] A comparison of the physical properties of the coatings obtained by dipping polyester fabrics in the coatings is shown in the table below.

[0097]

[0098]

[0099] It can be seen from the test results in the table that in Example 1, the coating that was immersed for 100 minutes and naturally dried for 4 hours was thicker, more evenly distributed, more completely cured, had a more complete intermolecular cross-linking reaction, and had the best physical properties such as hardness, scratch resistance, and wear resistance.

[0100] 2. Physical properties test of inner layer

[0101] Comparative Example 1 is only polyester fabric, and the inner layer prepared with Example 1 is tested and compared with the tensile breaking strength, bursting strength, tearing strength and contact angle performance.

[0102] The test method used for tensile breaking strength is the strip method. Specifically, cut the sample to ensure that the width of the sample is 200mm and the length is sufficient to ensure that the clamp spacing is 100mm. Set the clamp spacing of the tensile tester to 100mm, and select the load range so that the tensile force is between 30%-90% of the full scale. Set the tensile rate of the tester to 20mm / min. Clamp the sample in the clamp in the center, ensuring that the length direction of the sample is parallel to the direction of the tensile force. Start the tester and run it continuously until the sample breaks, and record the maximum load.

[0103] The test method used for bursting strength is hydraulic method. Specifically, clamp the sample in the clamp flatly, without tension and wrinkles, select the appropriate push rod diameter (such as 25mm or 38mm) and test speed (such as 100mm / min or 300mm / min), start the strength machine, apply liquid pressure under the diaphragm to expand the diaphragm and sample until the sample is burst, and record the maximum bursting strength value.

[0104] The test method used for the contact angle performance test is the sessile drop method, which is to drop a drop of liquid on the fabric surface, use a microscope or a high-resolution camera to photograph the droplet morphology, calculate the contact angle through a specific mathematical model, use an electronic balance to weigh the sample mass, place the sample in the center of the support plate, heat it to the test temperature, and transform the sample into a stable ellipsoidal droplet. Adjust the camera so that the ellipsoidal droplet is in the center of the video, and take a picture to obtain the image of the ellipsoidal droplet. Directly measure the angle between the tangent line of the contact point between the droplet and the fabric surface and the edge of the droplet.

[0105] The physical properties of the inner layer prepared in Example 1 and the comparative example 1 are compared and the data are shown in the following table.

[0106] Tensile breaking strength (N) Bursting strength(N) Contact Angle Comparative Example 1 573.92 652.34 85° Example 1 620.48 790.07 120°

[0107] It can be seen from the data in the table that compared with polyester fabric alone, polyester fabric plus silicone resin-based nano-titanium boride and titanium carbide composite coating not only fits the protected object but also has certain wear resistance and tensile resistance, and the tensile breaking strength is increased from 573.92N to 620.48N.

[0108] The bursting strength increased from 652.34N to 790.07N.

[0109] The hydrophobic performance is greatly improved, and the contact angle is increased from 85° to over 120°.

[0110] 3. Comparison of the protective effect of the outer protective layer

[0111] In Example 1, P120 coarse sandpaper was used for preliminary grinding, and P400 fine sandpaper was used for fine grinding. In Example 2, P100 coarse sandpaper was used for preliminary grinding, and P320 fine sandpaper was used for fine grinding. In Example 3, P80 coarse sandpaper was used for preliminary grinding, and P240 fine sandpaper was used for fine grinding.

[0112] The results of the sanding test using coarse sandpaper are shown in the following table.

[0113]

[0114] The test results of sanding with fine sandpaper are shown in the following table.

[0115]

[0116] 4. Comparison of the effects of internal honeycomb tube bundles

[0117] In Example 1, the D3O material is selected to be 1 mm lower than the frame made of thermoplastic elastic plastic TPE material, in Example 2, the D3O material is selected to be 1.5 mm lower than the frame made of thermoplastic elastic plastic TPE material, and in Example 3, the D3O material is selected to be 2 mm lower than the frame made of thermoplastic elastic plastic TPE material. The test results of different buffer layer thicknesses of Examples 1-3 are shown in the following table.

[0118]

[0119] It can be seen from the test results in the table that in Example 1, the D3O material is 1 mm lower than the frame made of thermoplastic elastic plastic TPE material, can be hardened in a very short time, and has the best protection when encountering a large impact force.

[0120] 5. Comparison of protective layers

[0121] The D3O material protective layer prepared in Example 1 was compared with the traditional soft and hard protective layers. The comparison results are shown in the following table.

[0122]

[0123] In summary, the D3O-based protective layer structure of the present invention has the properties of protection, energy absorption and wear resistance, wherein the wear resistance and tensile strength of the inner layer are significantly improved compared with polyester fabrics.

[0124] When the protective layer of the present invention is not subjected to collision or is subjected to a collision with a small or slight force, the D3O will not be hardened. The overall protective layer is soft and can better wrap the protected object. When subjected to a large-force collision such as a collision with a sharp object, the overall protective layer is quickly converted into hard protection to prevent the collision object from tearing and damaging the protected object.

[0125] The above embodiments are only used to illustrate the present invention, rather than to limit the present invention. Those skilled in the relevant technical field may make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions should also belong to the scope of the present invention and should be defined by the claims.

Claims

1. A D3O-based protective layer structure, characterized in that: It comprises an inner layer, an internal tube bundle layer and an outer layer which are arranged in parallel from bottom to top; the inner layer comprises polyester fabric and a silicone resin-based nano-titanium boride and titanium carbide composite coating coated on the polyester fabric; the internal honeycomb tube bundle layer comprises a honeycomb frame formed by a thermoplastic elastomer and a filler filled in the frame, and the filler is a D30 material; the outer layer is a butyl rubber layer.

2. A D3O-based protective layer structure according to claim 1, characterized in that: The coating used in the organic silicon resin-based nano-titanium boride and titanium carbide composite coating includes the following components in percentage by mass: The sum of the mass percentages of the above components is 100%. The coating amount of the organic silicone resin-based nano-titanium boride and titanium carbide composite coating on one side of the polyester fabric is 10-25 g / m 2 .

3. A D3O-based protective layer structure according to claim 2, characterized in that: The coating used for the inner layer of the organic silicon resin-based nano-titanium boride and titanium carbide composite coating includes the following components in percentage by mass: The coating amount of the organic silicon resin-based nano-titanium boride and titanium carbide composite coating applied on one side of the polyester fabric is 15-16g / m 2 .

4. The method for preparing a D3O-based protective layer structure according to claim 2, characterized in that: The method for preparing the coating used for the organic silicon resin-based nano-titanium boride and titanium carbide composite coating comprises the following steps: (1) Weigh each component according to the ratio, and heat the silicone resin to 50-60° C. under stirring to soften it; (2) adding the softened silicone resin and anhydrous ethanol in step (1) into a container, stirring at a speed of 300-500 r / min for 10-15 minutes, adding a hyperdispersant and an ethanol thickener, stirring for 20-30 minutes, and forming a mixed solution; (3) Adding nano titanium boride and nano titanium carbide to the mixed solution obtained in step (2), while increasing the stirring speed to 800-1000 r / min, stirring for 30-45 minutes, to obtain a coating for an organosilicon resin-based nano titanium boride and titanium carbide composite coating.

5. A D3O-based protective layer structure according to any one of claims 1 to 4, characterized in that: A fixed protection position is arranged on the protection layer, an outer protection layer is arranged at the fixed protection position, and the outer protection layer comprises a high-density polyethylene plastic layer and a polyurethane coating coated on the high-density polyethylene plastic layer.

6. A method for preparing a D3O-based protective layer structure as claimed in claim 5, characterized in that: The following steps are included: (1) Preparation of the inner layer: spray the coating used for the organic silicon resin-based nano-titanium boride and titanium carbide composite coating onto polyester fabric, dry it naturally for 3-5 hours, and make the coating evenly adhere to the polyester fabric to form an organic silicon resin-based nano-titanium boride and titanium carbide composite coating; or immerse the polyester fabric in the coating, take it out after immersion for 80-110 minutes, dry it naturally for 3-5 hours, and make the coating evenly adhere to the polyester fabric to form an organic silicon resin-based nano-titanium boride and titanium carbide composite coating; (2) Preparation of the internal honeycomb tube bundle layer: The thermoplastic elastomer material is melted and injected into the honeycomb tube bundle layer mold cavity. After curing, D3O material is filled in the hexagonal frame, and the height of the D30 material is 1-2 mm lower than the hexagonal frame; (3) Preparation of the outer protective layer: dust, oil and other impurities are removed from the surface of the polyethylene plastic, the surface is polished with coarse sandpaper, and then the surface is finely polished with fine sandpaper to clean the dust on the surface, and a polyurethane roller is applied to the surface of the polyethylene plastic, and cured by heating or ultraviolet light; (4) The inner layer, the inner honeycomb tube bundle layer, the outer layer and the outer protective layer are stacked and arranged in sequence, and an adhesive is used to bond them at the joints, and the adhesive is cured to obtain the protective layer.

7. The method for preparing a D3O-based protective layer structure according to claim 6, characterized in that: In step (3), the coarse sandpaper is P120 and the fine sandpaper is P400.

Citation Information

Patent Citations

  • Multifunctional high-strength composite fabric coating agent, coating, and preparation method and application of multifunctional high-strength composite fabric coating agent

    CN107254248A

  • Elastic shape memory material with shear thickening performance, and preparation method and applications thereof

    CN108424649A

  • Flexible lower limb safety protection device for paratrooper landing

    CN117562320A

  • Elderly tumble protective garment suitable for daily wearing

    CN210445760U

  • Protective tool

    CN221732328U

Cited By

  • Core pulling device of LED lamp cup shell injection mold

    CN120862992A

  • A core-pulling device of an injection mold for an LED lamp cup housing

    CN120862992B